2021
DOI: 10.3390/ma14247664
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Conventional Adhesive Application or Co-Curing Technique on Dentin Bond Strength

Abstract: The aim of this in vitro study was to assess the effect of two different adhesive application methods on shear dentin bond strength (ISO 29022) using three various adhesive systems. A mid-coronal section of 77 intact third human molars with fully developed apices was made to create flat bonding substrates. The materials used in the study were Excite F (Ivoclar Vivadent), Prime&Bond Universal (Dentsply Sirona) and G-Premio Bond (GC). The application of each adhesion system was performed in two different way… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…In the CLSM images of this study, polymerization without a clear boundary between the dentin adhesive and resin cement was observed for the co-curing group, indicating that the dentin adhesive and resin cement were polymerized together. However, several studies have reported reduced bond strength when the dentin adhesive is co-cured with resin cement [7,[20][21][22][23]. In this study, the bond strength between dentin and resin cement was signi cantly lower in co-curing groups than in light-curing groups (p < 0.05).…”
Section: Discussionmentioning
confidence: 52%
“…In the CLSM images of this study, polymerization without a clear boundary between the dentin adhesive and resin cement was observed for the co-curing group, indicating that the dentin adhesive and resin cement were polymerized together. However, several studies have reported reduced bond strength when the dentin adhesive is co-cured with resin cement [7,[20][21][22][23]. In this study, the bond strength between dentin and resin cement was signi cantly lower in co-curing groups than in light-curing groups (p < 0.05).…”
Section: Discussionmentioning
confidence: 52%
“…To further simplify the restorative procedure, the co-curing technique was introduced. In this technique, the polymerization of the primer/adhesive and the self-adhesive composite occurs simultaneously [ 23 , 37 , 38 ]. Notably, these groups exhibited three-fold higher bond strength values than the groups where etching was carried out as a stand-alone treatment.…”
Section: Discussionmentioning
confidence: 99%
“…It features the simultaneous curing of the primer and the flowable composite, which would allow the operator to skip a step, saving time and simplifying the procedure. However, it has shown conflicting results over the years [ 21 , 22 , 23 ]. In fact, neither the use of a primer by itself nor its co-curing with a self-adhesive composite have been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the occlusal plane of the lower jaw of each phantom head was adjusted parallel to the floor. For all teeth ( maxillary Fares, 2023 and mandibular ) ; the adhesive ( All -Bond Universal -BISCO -USA ), table (1) ; was applied to the flat dentin surfaces with a selfetch adhesion protocol and according to the manufacturers instructions. Then polytetrafluoroethylene molds ( each measuring 3 x 2 mm ) ; were placed onto the adhesive area of the teeth and light curing performed for 20 seconds, using an LED curing device ( Eighteeth -China ) with an intensity 1500 mw / cm2.…”
Section: Methodsmentioning
confidence: 99%
“…adhesive systems produce appropriate retention ( while conserving the sound tooth structure ) ; appropriate marginal sealing and favorable distribution of forces across the restorationtooth interface ( 1,2 ). Bond strength measurement is one of the most reliable methods for evaluating the adhesives clinical performance ( 2,8 ).…”
Section: Dentalmentioning
confidence: 99%